Death Audit of Patients admitted at Medicine Department: Experience of Largest Tertiary Care Hospital in Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Brain death is the irreversible end of all brain activity (including involuntary activity necessary to sustain life) due to total necrosis of the cerebral neurons following loss of brain oxygenation. In medical practice, common causes of death include stroke, acute myocardial infraction, heart failure, septicemia, COPD with respiratory failure, poisoning etc. Vital statistics outlining the major causes of death in a population are an important measure of public health.Objective: The aim of this study was to identify the causes of death from acute emergency and in chronic medical diseases with their demographic profiles.Methodology: It was a hospital based observational study, and the study period was 3 months (July, 2010 to September, 2010). The patients who died after admission in medicine ward of Dhaka Medical College Hospital were enrolled. The death certificate was collected from the office copy and the ICD code-based certificate writing was noted. The underlying cause of death, immediate cause of death and contributory cause of death was observed to understand the exact etiology of death in Medicine department.Results: The study group consisted of 100 subjects of whom 56 were male and 44 were female. Male: female ratio was 1.27:1. The age range was 18-90 years. Mean age was 49.34 for male and 42.94 for female. Death occurred in 45% cases within 24 hours, 49% cases from 1 to 7 days, 6% after 7 days. The major cause of death was stroke (26%) followed by poisoning (14%).Conclusion: The death audit revealed that the majority cases of death in medicine happen due to cerebrovascular accident and poisoning.Journal of National Institute of Neurosciences Bangladesh, January 2025;11(1):28-33